2018
DOI: 10.1021/acs.jpcc.8b07108
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Dopants on the Cu–ZrO2 Catalyzed Hydrogenation of Levulinic Acid

Abstract: Catalytic hydrogenation of levulinic acid to form γ-valerolactone was studied over Cu-ZrO2 catalysts doped with metal oxides from the first row transition metals. The Cu-ZrO2 material was prepared by oxalate gel co-precipitation and dopants were added by an incipient wetness approach. The addition of 1% Mn into Cu-ZrO2 significantly increases the yield of γ-valerolactone and the catalytic activity of Mn/Cu-ZrO2 was found to be 1.6 times higher than that of the undoped Cu-ZrO2 catalyst. Catalyst characterizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 52 publications
2
16
0
1
Order By: Relevance
“…Even so, additional cycling experiments ( Fig. 4 b) confirmed that the catalytic performance of the 30 mol% catalyst remained reasonably constant for up to 4 uses, which is a marked improvement compared with other Cu-ZrO 2 catalysts we have investigated previously (activity drop of up to 30% after 1 use) [28,32] . Perhaps most interestingly, SEM confirmed that there was severe change in the surface morphology of the catalyst upon subsequent uses, see Fig.…”
Section: Co-precipitation By a Ph Gradient Methodologysupporting
confidence: 60%
See 1 more Smart Citation
“…Even so, additional cycling experiments ( Fig. 4 b) confirmed that the catalytic performance of the 30 mol% catalyst remained reasonably constant for up to 4 uses, which is a marked improvement compared with other Cu-ZrO 2 catalysts we have investigated previously (activity drop of up to 30% after 1 use) [28,32] . Perhaps most interestingly, SEM confirmed that there was severe change in the surface morphology of the catalyst upon subsequent uses, see Fig.…”
Section: Co-precipitation By a Ph Gradient Methodologysupporting
confidence: 60%
“…Another study reported that the deposition of Pd onto a Cu-ZrO 2 could result in sequential reaction to produce 1,4-pentanediol and 2-methyl tetrahydrofuran [27] . We too have investigated how the doping of a secondary transition metal onto a Cu-ZrO 2 catalysts affects the performance [28] . Of the metals tested, only Mn provided a promotional effect which was established to be due to an increase in the rate of dissociative H 2 adsorption over the catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…The alarming predictions of the rapid depletion of fossil‐fuel resources have inspired researchers to develop alternative technologies that exploit renewable energy sources . Many studies have focused on the conversion of lignocellulosic biomass and triglycerides into various platforms of value‐added chemicals . Industrially, triglycerides in oils and fats have been used as feedstocks for the synthesis of fatty amines, amides, nitriles, and alcohols, which in turn are used for the production of surfactants, polymers, and other useful commodity chemicals …”
Section: Introductionmentioning
confidence: 99%
“…Selective hydrogenations over supported metal catalysts have been extensively studied since the discovery of the Lindlar catalyst for the hydrogenation of alkynes 1 because it is invaluable for the synthesis of various chemicals [2][3][4] as well as environmental purification. [5][6][7][8][9][10] A research goal in hydrogenation is to achieve high selectivity by optimizing the reaction conditions [11][12][13] in conjunction with catalyst design, wherein scientists search for the best combination of metal and support, [14][15][16][17] the addition of promoters, [18][19][20][21] and applying special preparation techniques and conditions.…”
Section: Introductionmentioning
confidence: 99%